Pharmacological Effect of Caulophyllum robustum on Collagen-Induced Arthritis and Regulation of Nitric Oxide, NF-κB, and Proinflammatory Cytokines In Vivo and In Vitro. (31st December 2017) - Wang, Qiu-hong; Lv, Shao-wa; Guo, Yu-yan; Duan, Ji-xin; Dong, Shu-yu; Wang, Qiu-shi; Yu, Feng-ming; Su, Hong; Kuang, Hai-xue
Abstract : Caulophyllum robustum Maxim (C. robustum) has commonly been used as traditional Chinese medicine for the treatment of rheumatic pain and rheumatoid arthritis (RA) in China. This paper first investigated the anti-inflammation effect of C. robustum extraction (CRME) on RAW264.7 cells stimulated by lipopolysaccharide (LPS) and gene expression levels of inflammatory factors. Moreover, we first evaluated the anti-RA effects of CRME using collagen-induced arthritis (CIA) in DBA/1J mice, and the incidence, clinical score, and joint histopathology were evaluated. The levels of IL-1, IL-6, TNF- α, and PGE2 inflammatory factors in sera of mice were detected by enzyme-linked immunosorbent assay. The expression of NF- κ B p65 in the joint was tested by immune histochemical technique. The results showed that, compared with the model group, CRME significantly improved symptoms of the arthritis index, limb swelling, and histological findings by decreasing synovial membrane damage, the extent of inflammatory cell infiltration, and the expansion of capillaries in CIA mice. The results also showed that CRME can reduce the levels of IL-1, IL-6, TNF- α, and PGE2 and inhibit the expression of NF- κ B p65. All these results indicated the anti-inflammatory efficacy of CRME as a novel botanical extraction for the treatment of RA.